Burden of hypertensive heart disease attributed to metabolic factors from 1990 to 2021 at global, regional, and national levels: an analysis of the global burden of disease study 2021 - Peng, Bo; Tu, Yuluo; Zhou, Cheng; Xie, Gui; Hu, Suifa; Zhuang, Jing; Huang, Kai; Xiong, Jia (Frontiers in Cardiovascular Medicine, 2025)
BackgroundMetabolic factors have an increasing impact on hypertensive heart disease (HHD). This study analyzes the global burden trends of HHD from 1990–2021, focusing on the contributions of high systolic blood pressure (HSBP) and high body mass index (BMI).MethodsThis study, based on the 2021 GBD database, analyzes the trends in deaths, disability-adjusted life-years (DALYs), age-standardized mortality rate (ASMR), and age-standardized DALY rate (ASDR) attributable to HSBP and high BMI from 1990–2021 at global, regional, and national levels. The estimated annual percentage change (EAPC) is used to assess the temporal dynamics of the disease burden, and the relationship between the disease burden and the sociodemographic index (SDI) is explored.ResultsIn 2021, deaths and DALYs due to HSBP and high BMI significantly increased compared to 1990. However, the ASMR for HSBP-related HHD [EAPC: −0.68; 95% confidence interval (CI): −0.77 to −0.58] and ASDR (EAPC: −0.90; 95% CI: −0.99 to −0.80) showed a decreasing trend, while the ASMR for BMI-related HHD (EAPC: 0.33; 95% CI: 0.27–0.39) and ASDR (EAPC: 0.15; 95% CI: 0.10–0.21) exhibited an increasing trend. From 1990–2021, the regions with the largest increases in ASMR and ASDR for HSBP-related HHD were Eastern Europe and High-income North America, while the largest increases for BMI-related HHD were seen in High-income North America. Moreover, most of the top 10 countries with the largest increases in ASMR and ASDR due to HSBP and BMI were from Eastern Europe. Additionally, in 2021, China had the highest number of deaths and DALYs globally due to HSBP and high BMI-related HHD. At the SDI level, Low SDI regions had the highest ASMR and ASDR for both HSBP and BMI-related HHD in 2021, with a negative correlation to overall SDI. Furthermore, deaths, DALYs, ASMR, and ASDR due to HSBP and BMI in females were generally higher than in males after the ages of 64 and 54, respectively, with the disease burden mainly concentrated in middle-aged and elderly populations.ConclusionsMetabolic factors are major risk contributors to HHD, with a disproportionately higher burden of mortality and DALYs observed among older adults, particularly women in later life stages. Given these trends, early identification and intervention in key populations should be prioritized through targeted public health strategies and multilayered interventions to mitigate the global burden of HHD and alleviate its growing strain on healthcare systems.